Revision of the genus Bryodemina Hull (Diptera, Bombyliidae, Lomatiinae) with descriptions of two new Neotropical species - Lamas, Carlos J.e.; Yamaguchi, Carolina; Evenhuis, Neal L. (Zootaxa, 2024)
The New World genus Bryodemina Hull is revised. Two new species are herein described and illustrated: Bry. enigmatica sp. nov. from Brazil and Bry. ayalai sp. nov. from Venezuela. The results of a detailed morphological study, based on types and material deposited in many collections of the world, shows that Brachydemia Hull should be considered as a junior synonym of Bryodemina Hull, syn. nov. and Bra. latisoma Hull as junior synonym of Bra. hedickei (Paramonov), syn. nov. Illustrations of the external morphology of adults and male and female terminalia for all valid species are presented. A distribution map including all examined records, an identification key to species together with a preliminary biogeographic discussion are also added.